2022
DOI: 10.1007/s10826-022-02286-1
|View full text |Cite
|
Sign up to set email alerts
|

Assisted Conception Socialization Self-Efficacy Among Israeli Lesbian, Gay, and Heterosexual Parent Families and its Association with Child Externalizing Problems

Abstract: This questionnaire-based study compared 36 Israeli lesbian mother families ( n = 72 lesbian mothers) formed by donor insemination, 39 Israeli gay father families ( n = 78 gay fathers) formed by gestational surrogacy, and 36 Israeli heterosexual parent families ( n = 72 heterosexual parents) formed by assisted reproduction (without donated gametes), all with a target child aged 3–10 years. The families were examined for parents’ assisted conce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
32
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 21 publications
(39 citation statements)
references
References 83 publications
(112 reference statements)
6
32
1
Order By: Relevance
“…Our results revealed that gay fathers through surrogacy reported more postnatal depressive symptomatology than heterosexual fathers. This does not conform with previous findings which detected no differences in depressive symptomatology between gay and heterosexual fathers [7,11,25]. An explanation for our results could be the time period of data collection.…”
Section: Discussioncontrasting
confidence: 99%
See 3 more Smart Citations
“…Our results revealed that gay fathers through surrogacy reported more postnatal depressive symptomatology than heterosexual fathers. This does not conform with previous findings which detected no differences in depressive symptomatology between gay and heterosexual fathers [7,11,25]. An explanation for our results could be the time period of data collection.…”
Section: Discussioncontrasting
confidence: 99%
“…Consistent with the literature discussed above regarding higher levels of hedonic and eudaimonic well-being among gay fathers through surrogacy in comparison to heterosexual fathers and posttraumatic growth among mothers contending with stressful birth events, we hypothesized that gay fathers through surrogacy will report greater life satisfaction and posttraumatic growth than heterosexual fathers. As most studies have not detected differences in depressive symptomatology between gay and heterosexual fathers e.g., [7,11] and there is a lack of data on postnatal depressive symptomatology among gay fathers [25], we did not consolidate a specific hypothesis regarding a difference in postnatal depressive symptomatology between the two groups.…”
Section: Research Hypothesesmentioning
confidence: 79%
See 2 more Smart Citations
“…Finally, sexual minority parents must play a key role in this process by preparing children to navigate stigmatizing experiences with resilience and forming positive family conceptualizations (Shenkman et al 2022). They may do so, for example, by ensuring age-appropriate open communication about their child's family background; discussing how best to handle questions, comments, and teasing; referring to print and digital media incorporating diverse family forms; and maintaining frequent contact with other children of sexual minority parents (Farr et al 2016a, Goldberg et al 2016, Oakley et al 2017, Wyman Battalen et al 2019.…”
Section: Discussionmentioning
confidence: 99%